Oil Rents and Income Inequality: The Moderating Role of Institutional Quality in Oil-Rich Developing Countries - Mehidi, Kahina; Oukaci, Kamal (Central European Journal of Economic Modelling and Econometrics, 2025)
The purpose of this study is to analyze the impact of oil rent on income inequalities. To this end, we selected a sample of 22 oil-rich developing countries and Norway as a benchmark country. The methodology employed in this work involves the use of a dynamic panel data specification over the period 2000-2022. The econometric results show the existence of a non-linear (inverted U-shaped) relationship between oil rent and inequality. Specifically, oil rent increases inequality in the short term. This effect diminishes as oil revenues increase. Another important finding is that the reduction of income inequality due to the increase in oil rent is closely related to the quality of the institutional framework.